Association of Sarcopenia With Toxicity and Survival in Postoperative Recurrent Esophageal Squamous Cell Carcinoma Patients Receiving Chemoradiotherapy - Xu, Ying-Ying; Zhou, Xi-Lei; Yu, Chang-Hua; Wang, Wan-Wei; Ji, Fu-Zhi; He, Dong-Cheng; Zhu, Wei-Guo; Tong, Yu-Suo (Frontiers in Oncology, 2021)
Background: Sarcopenia has been identified as a risk factor for toxicity and poor survival in various cancers. The aim of this study was to investigate the prevalence of sarcopenia in postoperative recurrent esophageal squamous cell carcinoma (ESCC) patients receiving chemoradiotherapy (CRT) and evaluate associations with treatment-related toxicity and prognosis. Methods: A total of 184 patients with postoperative locoregional recurrent ESCC treated with CRT Between January 2014 and December 2016 were included. The skeletal muscle area was measured by computed tomography at the third lumbar vertebra level. Sarcopenia was defined using the published cut-off values. Kaplan-Meier method and multivariate cox regression models were performed. Results: Sarcopenia was observed in 94 of 184 (51.1%) patients. Sarcopenic patients had significantly higher rates of grade 3-4 toxicities compared to those without sarcopenia (36.2% vs 21.1%, p = 0.034). The survival rate at 12 and 24 months was 36.2% and 3.2% in the sarcopenic patients and 57.8% and 17.8% in the non-sarcopenic patients (p < 0.001). On multivariate analysis, sarcopenia was identified as an independent prognostic factor for poor overall survival (HR = 1.729, 95% CI 1.231-2.428, p = 0.002). Conclusions: Sarcopenia is associated with treatment-related toxicity and poor survival in postoperative locoregional recurrent ESCC patients treated with CRT. Early nutritional interventions before treatment may improve the prognosis.